BIBLIOMETRIC ANALYSIS ON INTERNAL CORPORATE GOVERNANCE: WHAT IS THE NEXT RESEARCH? - Maulana, Ilham (Research In Management and Accounting (RIMA), 2022)
This study aims to internal corporate governance literature with a bibliometric analysis approach. To carry out this analysis, the data obtained from Dimensions with certain criteria are used, then mapping and analysis are carried out using VOSviewer and Bibliometrix. From the results of this analysis, researchers found the conceptual structure and intellectual structure used in the internal corporate governance literature. Then this research also found journals, authors, organizations, and countries that have the most significant contribution in the development of internal corporate governance. From the analysis that has been done, the researcher found that there are still topics of corporate control that researchers around the world rarely touch. This paper provides an overview of how the literature on internal corporate governance and provides an opportunity for further researchers to develop research on internal corporate governance